Genetic counseling clinical practice and ethical considerations - Hercher, Laura; Biesecker, Barbara; Austin, Jehannine C. (Cold Spring Harbor perspectives in medicine, 2020)
Genetic counselors advise patients and families affected by or at risk of genetic disorders. They educate them about inheritance, diseases, and screening tests, interpret medical histories and test results, and help families cope with diagnoses and make informed medical decisions. The profession is rapidly evolving and is poised to play an increasingly important role in society as genome sequencing becomes routine clinical practice. This collection from Cold Spring Harbor Perspectives in Medicine captures the current state of genetic counseling and examines the changing roles of genetic counselors in the genomic age. The contributors discuss the range of genetics-related needs people bring to counselors, existing and emerging technologies for genetic testing, challenges related to the abundance of recent discoveries about genetic diseases, the ways in which genetic counseling is integrated into modern medicine, and the expanding roles of genetic counselors beyond the clinical setting. The current and evolving practices in different counseling subspecialties, including infertility, prenatal care, pediatrics, cardiology, neurology, psychiatry, and cancer, are also covered. Other topics in the volume include ethical, legal, and social issues (e.g., genetic testing of minors, genetic discrimination, and obtaining informed consent for genomic testing), as well as the future of the profession. The volume is therefore an essential read for practicing genetic counselors, as well as all biomedical scientists and health professionals dedicated to using genetic and genomic information to improve the lives of individuals and their families.--Provided by publisher.